CHALLENGES OF ECONOMIC CRISIS TO INDEPENDENCE OF JUDICIARY - Žalimas, Dainius; Masnevaitė, Elena (Teisė, 2015)
Although independence of judiciary has become a universal principle, but in practice it is still sometimes subject to challenges. As the mission of the judiciary is to ensure legitimacy by defending human rights from arbitrary acts of other branches of state power, there is inevitable tension between the judiciary and other branches of state government. The executive and the legislature may sometimes seek to influence the court in various ways – influencing the selection and appointment of judges, decreasing the remuneration and other social benefits of judges, expressing will to limit the powers of the judiciary, refusing to implement judicial decisions or ignoring them. These and other threats to independence of the judicial are likely to increase during the economic crisis when the society suffers from asperities and is full of tensions. In order to achieve economic stabilization, human rights and freedoms, and its most significant protection guarantee – the independence of the judiciary, are often pushed to the background. Therefore it is often claimed that one of the consequences of the global economic recession is a global human rights crisis. The subject of this article is the specific challenges of the economic crisis of 2088–2012 in Lithuania posed to the main elements of the principle of judicial independence: independence of individual judges and institutional independence of the judiciary. These challenges are mostly related to two types of tension: the tension between law and politics, which arose due to verification and outlawing by the judiciary of some decisions of political power on the measures to overcome the economic crisis, and the tension between law and society, which arose due to the fact that the society not always accepted (or even was encouraged not to accept) the decisions of the judiciary assessing the legality of the measures taken by political power to overcome the economic crisis. This article aims to assess the impact of the economic crisis to the independence of the judiciary. The research done in this article seeks to verify the hypothesis that the guarantees of judicial independence (and human right to judicial defense) are diminished during the economic recession. The research was conducted by applying analytical, systematic, comparative, descriptive and quantitative analysis research methods. This research led to the conclusion that economic crisis threatened both the said elements of the principle of independence of the judiciary. The reduction of the most important social guarantees of a judge (salary, pension), i.e. the concrete measures found incompatible with the Constitution, can be regarded as an encroachment to the (procedural) independence of the judge. Reduced funding for the courts, taking into account the increased workload of the courts, as well as the reduced social guarantees of judges, can be seen as disproportionate anti-crisis measure that threatened the institutional independence of the judiciary. In addition to these challenges, the Constitutional Court due to its special role in assessing the anti-crisis measures also had to face significantly increased criticism by the representatives of the political branch of state government, which could be seen as a certain pressure on the Constitutional Court in the decision making process. Apart from that, these economic crisis challenges to independence of the judiciary has certainly influenced the public’s perception of the entire judiciary system and reduced public confidence in the judiciary, hence this situation has posed an immense threat to the appearance of independence of the judiciary. However, it should be noted, that the economic crisis has also lead to some positive reforms in the judicial system, which might not have been taken in a different situation – the adoption of procedural and other changes in the legislation, which was intended to promote the efficiency of judicial procedure, as well as the reorganization of some district courts, which helped to optimize the resources of those courts, and the inclusion of the representatives from the society into the activities of the judiciary system. Thus the above mentioned hypothesis has been confirmed in part, i.e. apart from the typical threats to the judicial independence, the economic crisis also opened some opportunities to optimize the judiciary activities increasing efficiency of judicial defense.